PATHOMORPHOLODY OF THE FETAL ADRENAL GLANDS IN ACUTE AND CHRONIC HYPOXIA (World Bulletin of Public Health, 2026)
One of the most important goals of the international public health system is the elimination of preventable infant and perinatal mortality (WHO, 2014) [1]. Key factors in the development of these changes include intrauterine fetal hypoxia and neonatal asphyxia, both acute and chronic. The adrenal gland is a key organ involved in the stress response. Despite this, data on the of the adrenal glands in acute and chronic hypoxia during the perinatal period remain incomplete and fragmented
Keywords: adrenal glands; fetus; perinatal mortality; hypoxia